A Revised Method for Analysing Neglect using the Landmark Task - Toraldo, Alessio; McIntosh, Robert D.; Dijkerman, H. Chris; Milner, A. David (Cortex, 2004)
In order to better disentangle ‘perceptual’ and ‘response’ biases in neglect patients, Bisiach and his co-workers developed a new version of the ‘landmark task’. In their version, subjects are required to choose which is the longer (first condition) or the shorter (second condition) of the two portions of a pre-bisected horizontal line. Two indices were proposed, for the purpose of measuring perceptual and response bias respectively. The perceptual bias index (PB) is the constant error across conditions, while the response bias index (RB) is the degree of response consistency between conditions. Although valuable in a clinical context, these indices are not mathematically independent of one another. Furthermore, they do not exploit all of the information available in a given set of landmark data, since the responses made at the different landmark locations are all averaged together. To overcome these problems, we propose two new indices that can be derived from the revised landmark task. Our perceptual bias index is the Point of Subjective Equality (PSE) – the mean landmark location that appears to be halfway along the line. The response bias index, M, is the mean probability of making a response that opposes the patient's subjective midpoint. PSE and M are mathematically independent of each other and use most of the landmark information. The method and its theoretical foundation are summarized, and illustrative data obtained from brain damaged patients and control subjects are presented. Finally, computational procedures are provided for both PSE and M.